Best responders after intensive upper-limb training for children with unilateral cerebral palsy - Sakzewski, L.; Ziviani, J.; Boyd, Roslyn (2011)
Objective: To delineate characteristics of best responders in a randomized trial comparing constraint-induced movement therapy (CIMT) to bimanual training for children with unilateral cerebral palsy. Design: Secondary analysis of a single-blind matched-pairs randomized comparison trial. Setting: Community sporting facilities in 2 Australian capital cities. Participants: Children (n=64; mean age, 10.2±2.7y; 52% boys), matched for age, sex, side of hemiplegia, and upper-limb function, were randomized within pairs to CIMT or bimanual training. Sixty-one children who completed CIMT (n=31) or bimanual training (n=30) were included in this study. Interventions: Each intervention was delivered in day camps (total 60h over 10d) using a novel circus theme with goal-directed training. Main Outcome Measures: Change between baseline, 3, and 26 weeks on the Melbourne Assessment of Unilateral Upper Limb Function (MUUL>7.4%), Assisting Hand Assessment (AHA>4 raw score points), and Canadian Occupational Performance Measure (COPM>2 points) defined best responders.Results: Poorer baseline hand function predicted a best response for unimanual capacity of the impaired upper limb (MUUL) immediately postintervention; however, at 26 weeks the odds of achieving a favorable outcome were 21 times greater for CIMT than bimanual training. A favorable response for bimanual performance (AHA) was predicted by immediate change in Jebsen-Taylor hand function test scores. Age (older), left-sided hemiplegia, and lower-baseline COPM performance scores significantly predicted favorable individualized outcomes. Conclusions: Secondary analysis of a randomized trial directly comparing 2 upper-limb training models, found children with poorer hand function benefited most. Favorable outcomes for bimanual performance were associated with gains in movement efficiency and older children with left-sided hemiplegia achieved more favorable gains in perceived occupational performance.